Macrophages, microglial cells, and HLA-DR antigens in fetal and infant brain. - Esiri, M M (1991)
Immunohistochemical reactions for macrophages, microglia, and HLA-DR antigens were tested on frozen sections of necropsy brain tissue from 20 fetuses and infants ranging in age from 18 weeks' gestation to 8 months post term. No primary central nervous system disease was present but there were four cases of sudden infant death syndrome (SIDS). Macrophages were detected in all the samples studied and were located in the germinal matrix zone, in perivascular spaces throughout the brain, and in the leptomeninges and subependymal layer. Well differentiated microglia were present in all cases examined after 35 weeks' gestation and less well ramified forms were seen at earlier stages of gestation. HLA-DR antigens were detected on a small number of macrophages, chiefly in a perivascular location, in all but three cases. The fewest reactive cells and the weakest reactions occurred in the youngest fetuses. One case of SIDS showed increased foci of microglia in perivascular white matter: this case and one other case of SIDS were the only cases with well ramified microglia that expressed HLA-DR antigens. These findings may be relevant to an understanding of local immune responses in fetal brain infections, including human immunodeficiency virus infection.